1996
DOI: 10.1046/j.1365-2648.1996.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance: recognition of factors involved and suggestions for promoting compliance with therapeutic regimens

Abstract: Patient compliance is paramount in the effectiveness of therapeutic regimens. Without compliance therapeutic goals cannot be achieved, resulting in poorer patient outcomes. The social and psychological factors thought to influence compliance are identified as (a) knowledge and understanding including communication, (b) quality of the interaction including the patient-provider relationship and patient satisfaction, (c) social isolation and social support including the effect of the family, (d) health beliefs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
200
0
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(219 citation statements)
references
References 32 publications
8
200
0
11
Order By: Relevance
“…29 Social isolation was strongly associated with noncomprehension of the exercise instructions in this study, adding to prior reports of social isolation as a predictor of non-compliance. [30][31][32] Cognition and high school education were not associated with non-comprehension in any domain of the discharge instructions, although health literacy has been previously identified as a barrier to comprehension. 1,2,6,8 Factors associated with non-comprehension may help identify patients at greater risk, but do not provide a rationale for non-comprehension.…”
Section: Discussionmentioning
confidence: 72%
“…29 Social isolation was strongly associated with noncomprehension of the exercise instructions in this study, adding to prior reports of social isolation as a predictor of non-compliance. [30][31][32] Cognition and high school education were not associated with non-comprehension in any domain of the discharge instructions, although health literacy has been previously identified as a barrier to comprehension. 1,2,6,8 Factors associated with non-comprehension may help identify patients at greater risk, but do not provide a rationale for non-comprehension.…”
Section: Discussionmentioning
confidence: 72%
“…It is important that information provided is clear, that there is no ambiguity and that patient needs be evaluated periodically. 22 The primary motive for failures to administer chemotherapy was forgetfulness. This finding is compatible with other reports in the literature which have found that forgetfulness, worries and lack of medication were the motives most often cited by parents of cancer patients to explain medication compliance failures.…”
Section: Discussionmentioning
confidence: 99%
“…(Goold & Lipkin, 1999). If a pregnant woman with a raised BMI perceives their doctor to have judgemental attitudes, this will be given disproportional weight and likelihood of ongoing engagement with care may decrease (Goold & Lipkin, 1999;Cameron, 1996).…”
Section: Strengths and Limitationsmentioning
confidence: 99%